Use and commercialization of Podocnemis expansa (Schweiger 1812) (Testudines: Podocnemididae) for medicinal purposes in two communities in North of Brazil - Santana Gindomar G; Alves Rômulo RN (Journal of Ethnobiology and Ethnomedicine, 2008)
Abstract Background Throughout Brazil a large number of people seek out reptiles for their meat, leather, ornamental value and supposed medicinal importance. However, there is a dearth of information on the use of reptiles in folk medicine. In North Brazil, the freshwater turtle, Podocnemis expansa, is one of the most frequently used species in traditional medicines. Many products derived from P. expansa are utilized in rural areas and also commercialized in outdoor markets as a cure or treatment for different diseases. Here we document the use and commercialization of P. expansa for medicinal purposes in the state of Pará, Northern Brazil. Methods Data were gathered through interview-questionnaires, with some questions left open-ended. Information was collected in two localities in Pará State, North of Brazil. In the City of Belém, data was collected through interviews with 23 herbs or root sellers (13 men and 10 women). Attempts were made to interview all animal merchants in the markets visited. In fishing community of the Pesqueiro Beach, interviews were done with 41 inhabitants (23 men and 18 women) and during the first contacts with the local population, we attempted to identify local people with a specialized knowledge of medicinal animal usage. Results P. expansa was traded for use in traditional medicines and cosmetics. Fat and egg shells were used to treat 16 different diseases. Turtle fat was the main product sold. The demand for these products is unknown. However, the use of this species in folk medicine might have a considerable impact on wild population, and this must be taken into account for the conservation and management of this species. Conclusion Our results indicated that the use and commercialization of P. expansa products for medicinal purposes is common in North of Brazil. More studies regarding the use and commerce of Brazilian turtles are urgently needed in order to evaluate the real impact of such activities on natural populations. We hope that our findings about the trade and use of P. expansa in folk medicine will motivate further studies on the use of animals in folk medicine and its implications for conservation.